Analytical Behavior of CFST Bridge Piers under Cyclic Loading. (2017) - Yadav, Raghabendra; Chen, Baochun; Yuan, Huihui; Lian, Zhibin
Abstract: Concrete filled steel tube (CFST) columns are widely used in civil engineering structures due to its abundant structural benefits like excellent seismic behaviour, ultimate load bearing capacity, fire resistivity, excellent ductility and energy absorption capacity, particularly in zones of high seismic risk. In this paper, the numerical study on seismic behaviour of CFST bridge piers are carried out by using Open SEES. The lateral load carrying capacity under cyclic load is investigated due to the change in different parameters like diameter-to-thickness (D/t) ratio, steel grade, concrete grade, and slenderness ratio. Results shows that the lateral load capacity significantly increased by D/t ratio, increase in steel grade and decrease in slenderness ratio and slightly increase due to increase of concrete grade.